Inflación del capital natural de la dehesa: hipótesis sobre la naturaleza caótica de la seca de los Quercus DENTRO DEL PROCESO DE LA SENESCENCIA FOLIAR - CUEVAS, S; TORRES, E; VÁZQUEZ, F.Mª.; López Arias, M; HERNÁNDEZ, A (III Congreso Forestal Español Congreso, 2001)
“Dehesa” is a gap forest yielding as an ecological-economic system (money-borrowed), poor soils (money-lender) upheld during optimal stopping millenia. Have supported multiple antropogenic nutrition disturbances during chaotic and resource routine affecting oak root uptake. Shoot nutrient odyssey is represented by cobweb model as price (nitrogen) evolution working by-product quantity (biomass). This trial evaluates cork oak (Quercus suber L.) and holm oak (Quercus rotundifolia Lam.) harvest basic sustainability (HBS) or nitrogen leaf redemption, southern Extremadura situated, evaluating ecological economic orientor for ecosystem. Defective HBS management hypothesis is expound in the absence of forest management, leading to sickly phenomenon on forest health as oak decline. Parallelly, HBS is proposed as an cork quality indirect index. Leaf senescence fork leads to physiological imbalance and, in some final cases, whole canopy defoliation (tie break). K.W.: Cobweb model, Oak decline, Renewal, Optimal stopping Dehesa, Nitrogen.
Keywords: Cobweb model; nitrogen; Oak decline; Optimal stopping Dehesa; Renewal

El ciclo de biomasa en bosques de frondosas del sur de extremadura. variabilidad espacial del desfronde - TORRES, E; CUEVAS, S; VÁZQUEZ, F Ma; SUÁREZ, Ma A (II Congreso Forestal Español, 1997)
The knowledge of the biomass and nutrients cycle is very important for a suitable forest management. In this paper, four broadleaved species litterfall, during november 1996, is studied in Extremadura (Spain): Castanea sativa Miller, Quercus pyrenaica Willd, Q. rotundifolia Lam and Q. suber L. Litterfall is compared in sorne forests with different maturity. Also, orientation, position and individual tree factors influence is analysed
Keywords: Castanea sativa; Extremadura; litterfall; Quercus pyrenaica; Quercus rotundifolia; Quercus suber

FORESTACIÓN CON CUATRO ESPECIES (Quercus coccifera L., Q.faginea Lam., Q. rotundifolia y Q. suber L.) DE FRONDOSAS EN EXTREMADURA P.M. - Vázquez, F M; Suárez, M A; TORRES, E; CUEVAS, S (II Congreso Forestal Español, 1997)
The principal species of interest in order to form forests of mediterranean type (not of riverside) in the South half of the Iberian Peninsula are the genus Quercus L ones. In this work the outputs contrasted of development are introduced, 1 root and systems of protection utilized in a mixed afforestation with four species of the cited genus (Q. coccifera L., Q. faginea Lam., Q. rotundifolia Lam., Q. suber L.), in Extremadura (Spain). The analysis of the data offers different strategies in sylviculture for the forest recuperation of the zone in function of the species that utilize
Keywords: Afforestation; coccifera; Extremadura; faginea; Quercus; rotundifolia; suber; sylvicuIture

INFLUENCIA DE LA DENSIDAD DE LA MASA EN LA CALIDAD Y PRODUCCION DE CORCHO EN LOS ALCORNOCALES DE CORTES DE LA FRONTERA (MALAGA) - Montero, G; TORRES, E; Suárez, M A; Ortega, C (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The influence of stand density on cork yield was evaluated for the Cortes de la Frontera (Spain) cork oak stand. Fifty five experimental plots were installed. The modular values of several variables which define cork oak yield potential of a tree, are presented by stand densitY'clusters (basal area groups). Likewise, many stand variables for different basal areas were studied
Keywords: cork-oak; silviculture; stand density

LIMITACIONES A LA REGENERACIÓN NATURAL DE LOS ALCORNOCALES EN EL PARQUE NACIONAL DE DOÑANA (HUELVA, ESPAÑA) P.M. - VÁZQUEZ, P M; Suárez, M A; TORRES, E (II Congreso Forestal Español, 1977)
The possible limitations to the in several experiences natural regeneration of the Quercus suber L. in a guarded area (Doñana) are undertaken in this study. The outputs offer a global vision of the natural regeneration in the Doñana's National Park. The production of seeds the sanitary state of the hoisted and their plagues, the attack of the spineless on the fruits and the climate don't harm the process of the natural regeneration in the -forest of Q. suber L. However the animal pressure (mammals), and the load cattle are the two factor s that impede the natural regeneration of the cork oak in Doñana. Finally, different strategies are contributed in order to recuperate the cork oak: fence, sowing, plantation and descent of the pressure animal in the zone.
Keywords: cork-oak; Doñana; natural regeneration; Quercus suber L.; silviculture